2018
DOI: 10.1007/s13139-018-0524-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 68Ga-DOTATOC Uptake in the Thoracic Aorta and Its Correlation with Cardiovascular Risk

Abstract: Ga-DOTATOC uptake in the thoracic aorta exhibited a significant correlation with cardiovascular risk factors, which suggests the feasibility of Ga-DOTATOC PET for vulnerable plaque imaging, with a simple measurement of the single VOI method that is comparable to the multi-sample ROI-based approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In a study of 32 patients who underwent PET imaging with the TSPO radioligand 11 C-PK11195, culprit carotid plaques associated with stroke or transient ischaemic attack where highlighted by the tracer [10]. In this study, 11 C-PK11195 signals were F-FEDAA1106 [11] F-FEMPA [12] F-GE-180 [13] TSPO Activated macrophages Inflammatory cell recruitment/activity Ga-DOTATATE [14,18,19] Cu-DOTATATE [20,21] Ga-DOTANOC [18] F-FDR-NOC [18] Ga-DOTATOC [21,22] SST 2 F-flutemetamol [64] Amyloid n/a Amyloid within plaque confirmed in macrophage-rich plaque areas when examined histologically [10]. Other TSPO tracers that have potentially lower non-specific binding than 11 C-PK11195 and are less affected by genetic polymorphisms leading to variable receptor binding affinity are being investigated [11][12][13].…”
Section: Tracers For Imaging Inflammatory Cellsmentioning
confidence: 72%
See 1 more Smart Citation
“…In a study of 32 patients who underwent PET imaging with the TSPO radioligand 11 C-PK11195, culprit carotid plaques associated with stroke or transient ischaemic attack where highlighted by the tracer [10]. In this study, 11 C-PK11195 signals were F-FEDAA1106 [11] F-FEMPA [12] F-GE-180 [13] TSPO Activated macrophages Inflammatory cell recruitment/activity Ga-DOTATATE [14,18,19] Cu-DOTATATE [20,21] Ga-DOTANOC [18] F-FDR-NOC [18] Ga-DOTATOC [21,22] SST 2 F-flutemetamol [64] Amyloid n/a Amyloid within plaque confirmed in macrophage-rich plaque areas when examined histologically [10]. Other TSPO tracers that have potentially lower non-specific binding than 11 C-PK11195 and are less affected by genetic polymorphisms leading to variable receptor binding affinity are being investigated [11][12][13].…”
Section: Tracers For Imaging Inflammatory Cellsmentioning
confidence: 72%
“…Another study, of 64 Cu-DOTATATE, also found this tracer to be useful for identifying carotid artery inflammation in patients with transient ischaemic attack and identified an association with gene expression of markers in macrophages [ 20 ]. Several other clinical somatostatin receptor binding tracers have also been examined for use in atherosclerosis imaging [ 18 , 21 , 22 ].
Fig.
…”
Section: Novel Pet Tracers For Imaging Atherosclerosismentioning
confidence: 99%
“…Ga-68 DOTATATE does not demonstrate significant myocardial uptake, making it an excellent tracer for imaging of inflammation in coronary plaques. Using Ga-68 DOTATOC, Lee et al confirmed the correlation between arterial tracer uptake and patients' Framingham risk score (Lee et al 2018). Ga-68 has a longer positron range compared with F-18, hence PET imaging with Ga-68 suffers from a lower spatial resolution.…”
Section: Somatostatin Receptor-based Imagingmentioning
confidence: 99%
“…1 21 and summarized in the Table 1 . 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 In particular, we focus on Na[ 18 F]F PET/CT in the following section.…”
Section: Overview Of Molecular Imaging For Atherosclerosismentioning
confidence: 99%